Religious Elites and Social Media: Contribution in Creating Peace - Feiby Ismail , Sri Rahmi, Mardan Umar, Zainal Arifin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The religious elite plays an important role in shaping the understanding and practice of people in religion. Every delivery of his da’wah will be a reference for the people in dealing with a problem. Therefore, the religious elite are required to offer invitations to goodness and peace. This study aims to analyse the activities of religious elites on social media in bringing peace especially in Manado, North Sulawesi, Indonesia. The study also seeks to recognize the role of the religious elite in responding to provocative news on social media. Data were collected on selected samples by interviews, observations, and surveys on social media activities, and is assisted with Google forms using semantic and pragmatic methods. Data were analyzed by examining the types of semantic meanings, based on the presence or absence of taste values, the accuracy of meaning, the relationship of meaning to one another, and pragmatic meaning based on the type found from selected social media content samples. The results obtained from social media analysis indicated that the activities of religious elites on social media can be categorized into two groups, namely active and passive users. Active Users often publish personal and group activities, provide religious advice and wise sentences, while passive users only read and do not give excessive responses to issues and